The DIY bride, an affair to remember : 40 fantastic projects to celebrate your unique wedding style - Cochran, Khris (Taunton Press, 2012)
"Hip and crafty brides-to-be understand the value of doing it themselves. Not only is taking a hands-on approach to nuptials a great way to save money, but it allows brides-to-be everywhere to showcase their own personal style. Author Khris Cochran, the wedding world's craft guru, understands how an engaged gal today plans and designs her wedding. The creator of DIYBride.com and author of two highly successful DYI Bride books, she has packed this third volume with 40 brand new fun and original projects. Organized by wedding theme, including Sand & Sea, Bright Lights, Big City, and A Touch of Country, The DIY Bride An Affair to Remember includes themed projects for save-the-dates, invitations, programs, favors, decorations, and more. A popular price comparison box shows how much these DIY projects can save; a budget section itemizes the costs; and a new box offers extra style variations. With 80 inspiring photos, this is the book brides will say "I do" to for a one-of-a-kind wedding"--